THE CONDITION OF CORAL REEFS IN THE WATERS OF TIDUNG ISLAND KEPULAUAN SERIBU JAKARTA - Muhammad Hafiz Perdana; Thamrin Thamrin; Nursyirwani Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The aims of this study are to determine the condition of the coral reefs including percentage live coral cover, the diversity index, the uniformity index, and the dominance index of lifeform coral at waters of Tidung Island Kepulauan Seribu Jakarta. This research has been conducting from 2018 May 7th - 17th at the waters of Tidung Island.The research station was divided into 3 stations based on environmental characteristics with 2 different depths ; 3 and 7 meters. The research station is a coral conservation area, snorkeling area, and natural area. Data of coral reef was obtained by using the Line Intercept Transect (LIT) method. The results showed that the conditions of coral reefs at stations 1 and 2 respectively in the bad category with the percentage of cover area are 3.52% and 10.84%. Whereas at station 3 the condition of coral reefs is in the medium category with the percentage of cover area is 30.01%. The low percentage of coral cover is caused by rising sea water temperatures, port activities and human activities. Water quality such as temperature, salinity, pH, current velocity and brightness at the study site is quite good for coral recovery and growth. Keyword : LIT, Coral Recovery, Diversity, Uniformity, and Dominance Index